Mapeamento cruzado de intervenções de enfermagem para adultos e idosos hospitalizados com diagnóstico de risco de integridade da pele prejudicada - Meneses , Lenilma Bento de Araújo (2016)
Introduction: With the Nursing Process arise Ratings Systems of Nursing Practice, starting with the nursing diagnosis classification, then classification of nursing interventions and Classification of Nursing Outcomes, constituting a comprehensive standardized language system of nursing practice. Objective: To analyze from the cross mapping, nursing interventions / activities, described by nursing students for the diagnosis Integrity Risk of Skin adults Impaired and hospitalized elderly, correlating them to the Nursing Interventions Classification, according to NANDA- link I / NIC, 2007 - 2008; Identify nursing interventions / activities described by nursing students for the diagnosis Integrity Risk of Skin impaired adults and elderly hospitalized; conduct cross-mapping of nursing interventions / activities, described by nursing students for the Health Risk diagnosis Impaired skin of adults and elderly hospitalized, comparing them to the classification; validate the content of nursing interventions / activities, described by nursing students to diagnose Integrity Risk of Skin Impaired of hospitalized adults and elderly, by specialist nurses. Method: a descriptive study, quantitative approach, used cross mapping. Held at the Federal University of Paraiba, with 25 nursing students and 14 nurses. Attended Resolution 466/2012. Data collection took place in three phases, the analysis based on descriptive statistics. The thesis is in articles format. Results: Mapped up with the Classification of Nursing Interventions, 32 interventions and 78 nursing activities in the fields: Physiologic complex, basic, behavioral and physiological safety. Interventions mapped 24 are in connection 8 and beyond. Conclusions: validated to 11 nursing interventions as a priority and 21 as suggested. It was identified focus on priority interventions, except for "Care bed rest," he said to the activities of "facilitating self-care", it is concluded that it is important to strengthen the teaching of this subject in nursing education.